PELAKSANAAN PENERAPAN SANKSI ADAT NGAMPANG MENURUT HUKUM ADAT DAYAK KANTUK DI DESA KEDAMIN DARAT - NIM. A1011201199, DEA CISRA ARORA (Jurnal Fatwa Hukum, 2025)
ABSTRACT                               The people of Kedamin Darat Village are people who still uphold traditional values in their lives. Like the Ngampang traditional sanctions that they still carry out today. By holding traditional sanctions, it is a process of purifying the village and hoping that these sanctions can have a deterrent effect and can minimize the occurrence of adultery, especially among young people. However, the implementation of Ngampang traditional sanctions in Kedamin Darat Village has shifted, such as the Ngampang customary payment fine in the form of objects that can be replaced with nominal money.                               The formulation of the problem in this study is whether the Ngampang customary sanctions on the Dayak tidur community in Kedamin Darat Village are still being implemented. This study aims to describe, obtain data, and information about Ngampang customary sanctions. In this study, the author uses a descriptive empirical research method, the purpose of this study is to obtain data and information on Ngampang customary sanctions, procedures for resolving Ngampang customary sanctions, legal consequences for perpetrators of Ngampang acts and efforts made by the customary leader to perpetrators of Ngampang acts.                                                 The results achieved that the implementation of Ngampang customary sanctions on the Dayak Kantuk community in Kedamin Darat Village is still being implemented until now, Factors that cause Ngampang acts are lack of supervision or attention from parents, free association, technological and communication advances such as misuse of the internet to watch pornographic videos, and lack of community reaction when seeing men and women who are together in a quiet and dark place. The legal consequences for perpetrators who commit Ngampang acts will be subject to material sanctions and moral sanctions, namely by paying customary fines and perpetrators of Ngampang acts are not free from insults, reproaches, and gossip from the community. The efforts made by the customary leader for perpetrators of Ngampang customary violations are that the customary leader will summon the two Ngampang perpetrators along with their parents or families of both parties to hold a customary trial and carry out a customary ceremony as a form of eliminating sins and purifying the village for the actions they have committed.  Keywords: Dayak, Kantuk, Ngampang, Sanctions, ImplementationABSTRAK                                Masyarakat Desa Kedamin Darat merupakan masyarakat yang masih menjujung tinggi nilai adat dalam kehidupan mereka. Seperti halnya sanksi adat Ngampang yang masih mereka laksanakan hingga sekarang. Dengan diadakannya sanksi adat merupakan suatu proses pensucian kampung dan mengharapkan adanya sanksi tersebut dapat memberi efek jera serta dapat meminimalisir terjadinya perzinahan terutama di kalangan pemuda/i. Namun penerapan sanksi adat Ngampang di Desa Kedamin Darat mengalami pergeseran seperti denda pembayaran adat Ngampang berupa benda yang dapat diganti dengan nominal uang.                               Rumusan masalah dalam penelitian ini yaitu apakah sanksi adat Ngampang pada masyarakat Dayak kantuk di Desa Kedamin Darat masih dilaksanakan. Penelitian ini bertujuan untuk menggambarkan, mendapatkan data, dan informasi tentang sanksi adat Ngampang. Dalam penelitian ini Penulis menggunakan metode penelitian empiris yang bersifat deskriptif, tujuan penelitian ini adalah untuk memperoleh data dan informasi sanksi adat Ngampang, tata cara penyelesaian sanksi adat Ngampang, akibat hukum bagi pelaku perbuatan Ngampang dan upaya yang dilakukan ketua adat kepada pelaku perbuatan Ngampang.  Hasil yang dicapai bahwa penerapan sanksi adat Ngampang pada masyarakat Dayak Kantuk di Desa Kedamin Darat masih dilaksanakan sampai sekarang, Faktor yang menyebabkan terjadinya perbuatan Ngampang adalah kurangnya pengawasan atau perhatian dari orang tua, pergaulan bebas, kemajuan teknologi dan komunikasi seperti penyalah gunaan internet untuk menonton video porno, serta kurangnya reaksi masyarakat jika melihat laki-laki dan perempuan yang berduaan di tempat sepi dan gelap. Adapun akibat hukum bagi pelaku yang melakukan perbuatan Ngampang akan dikenakan sanksi materil dan sanksi moral, yaitu dengan membayar denda adat dan pelaku perbuatan Ngampang tidak terlepas dari hinaan, celaan, dan gunjingan masyarakat. Upaya yang dilakukan ketua adat bagi pelaku pelanggaran adat Ngampang adalah ketua adat akan memanggil kedua pelaku Ngampang beserta orang tua atau keluarga kedua belah pihak untuk melakukan sidang adat dan melaksanakan upacara adat sebagai bentuk penghapusan dosa dan mensucikan kampung atas perbuatan yang telah mereka lakukan.   Kata Kunci : Dayak, Kantuk, Ngampang, Sanksi, Penerapan